The Effects of a Citywide Bike Share System on Active Transportation Among College Students: A Randomized Controlled Pilot Study. (June 2020) - Grimes, Amanda; Baker, Michele
Introduction. Despite the known health benefits of biking, within the last year, 46% of college students reported not riding a bike. This trend indicates a need to explore interventions to increase bicycling. The purpose of this study was to examine how a free membership to a citywide bike share system, with a campus docking station, affected bicycling and physical activity. Method. Undergraduate students were recruited from a Midwest University to participate in this research study in spring 2018. Each participant wore an activity-tracking device for 3 weeks and was randomly assigned to either an intervention group ( n = 29) or a control group ( n = 27). Participants in the intervention group received a free 1-month membership to Kansas City's bike share system, B-cycle. Data on the type of activity (e.g., biking), the frequency, duration, and overall steps were collected. A pre- and posttest survey was developed and distributed to assess perceptions and use of bicycles and the bike share system. T tests were performed to identify differences between the two groups. Results. Data analyses reveal no significant differences in overall steps or increased biking behavior between the two groups. Furthermore, only two of participants who received a free bike share membership redeemed their membership. Among other barriers, risk of overage fees or not wanting to enter credit/debit card information emerged as major themes that deterred participants. Conclusions. Results from this study will inform future interventions to decrease barriers, increase physical activity, and increase the proportions of trips taken by bike among college students. More specifically, alternative payment methods should be explored to decrease the barriers observed.